Markers of gut mucosal inflammation and cow's milk specific immunoglobulins in non‐IgE cow's milk allergy. Issue 1 (5th March 2014) - Merras‐Salmio, Laura; Kolho, Kaija‐Leena; Pelkonen, Anna S; Kuitunen, Mikael; Mäkelä, Mika J; Savilahti, Erkki
Abstract: Background: Allergy to cow's milk protein (CMP) may cause gastrointestinal (GI) symptoms in the absence of CMP specific IgE. The immunological mechanisms involved in such disease are not fully understood. Therefore we examined markers of gut mucosal inflammation and the immunoglobulin profiles in children with Gl symptoms suspected of cow's milk protein allergy (CMPA). Patients and methods: We prospectively recruited infants and young children (n = 57; median age 8.7 months) with gastrointestinal complaints suspected of CMPA. The diagnosis of CMPA was made using the double‐blind, placebo‐controlled food challenge. Serum and stool samples were collected during CMP‐free diet and after both placebo and active challenges. We analyzed the stool samples for calprotectin, human β‐defensin 2 and IgA. In serum, we analyzed the levels of β‐lactoglobulin and α‐casein specific IgA, and IgG antibodies (total IgG and subclasses IgG1 and IgG4). Control group included children with e.g. dermatological or pulmonary problems, consuming normal diets. Results: Fecal calprotectin levels were higher in the challenge positive group (n = 18) than in the negative (n = 37), with respective geometric means 55 μg/g [95% confidence interval 38–81] and 29 [24–36] μg/g (p = 0.0039), during cow's milk free diet. There were no significant inter‐group differences in the fecal β‐defensin and IgA levels. The CMP specific IgG and IgA were not elevated in patients with CMPA, but the levels of β‐lactoglobulin‐IgG4 (p = 0.0118) and α‐casein‐IgG4 (p = 0.0044), and total α‐casein‐IgG (p = 0.0054) and ‐IgA (p = 0.0050) in all patient samples (regardless of CMPA diagnosis) were significantly lower compared to the control group using dairy products. Conclusions: Despite cow's milk elimination in children intolerant to cow's milk there might be ongoing low‐grade inflammation in the gut mucosa. CMP specific IgG or IgA should not be used to diagnose non‐IgE CMPA. The observed frequency of impaired CMP specific total IgA, IgG and IgG4 production in patients following cow's milk free diet warrants further studies.